PROBLEMS IN THE HANDLING OF LARGE SECTIONS IN ACCOUNTING BY THE LECTURE METHOD. - Mason, Perry (The Accounting Review, 1948)
Abstract The article presents an overview of the problems which arise in connection with the lecture method in accounting. The University of California has for some time been noted for an extensive use of large lectures in many courses, including some of the courses in accounting. The men in charge of the laboratory work in the advanced courses have the rank of Associate, have a master's degree and are working towards the doctorate. Those in charge of the sections in the elementary course ordinarily are graduate students working towards the MBA degree, and they are given the title of Teaching Assistant. There are five lecture sections in elementary accounting, including both semesters of the course. Correlation of the lecture and laboratory sessions is another problem. Attempts are made to work out an approximately uniform procedure for handling the lectures and laboratory work, particularly as to the emphasis which is to be placed upon certain points. Lectures alone without the laboratory would certainly be very ineffective. A group of good graduate students can often do a better job for the beginning students than a group of part-time instructors drawn from accounting practice.